2013
DOI: 10.1016/j.sjopt.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of posterior chamber phakic intraocular lens procedure to correct myopia

Abstract: Implantation of ICL for the correction of myopia was a safe procedure with good visual and refractive results from the early postoperative period to 1 year. Long-term follow-up is required to confirm the long-term safety of this implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
0
12
0
2
Order By: Relevance
“…Previously published ICL reports have also documented an improvement in BCVA after ICL implantation. 3 BCVA was maintained or improved in all eyes in the series published by Senthil S et al 1 , Sabaani A et al 2 and Le Loir M et al 4 whereas only one eye lost BCVA in studies by Baradaran-Rafii A and Hashemian SJ et al 5 and Zaldivar et al 3,5 In our study, Postoperative examinations were conducted at day 1, day 3, after 1 week, 1 month and after 3 months. Comparing the proportion of eyes with 6/24 or better BCVA, only 68% had this level pre operatively, compared with 96% of eyes had this level at the postoperative visit which indicates the efficacy of phakic IOL.…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…Previously published ICL reports have also documented an improvement in BCVA after ICL implantation. 3 BCVA was maintained or improved in all eyes in the series published by Senthil S et al 1 , Sabaani A et al 2 and Le Loir M et al 4 whereas only one eye lost BCVA in studies by Baradaran-Rafii A and Hashemian SJ et al 5 and Zaldivar et al 3,5 In our study, Postoperative examinations were conducted at day 1, day 3, after 1 week, 1 month and after 3 months. Comparing the proportion of eyes with 6/24 or better BCVA, only 68% had this level pre operatively, compared with 96% of eyes had this level at the postoperative visit which indicates the efficacy of phakic IOL.…”
Section: Resultsmentioning
confidence: 46%
“…several studies reported an improvement in BCVA after ICL implantation with no accompanying intraoperative or postoperative complications. 3 Preservation of BCVA, commonly considered the primary criterion for assessing the safety of a refractive surgical procedure, was extremely high in the study cohort presented in this article. Previously published ICL reports have also documented an improvement in BCVA after ICL implantation.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Die implantierbare Collamer-Linse (ICL) stellt eine effektive sichere operative Alternative [2] für die Korrektur einer moderaten bis hohen Myopie mit langfristig guten Ergebnissen [1,2,21,22] dar. Die Indikation für die ICL-Implantation besteht bei gesunden Patienten, bei denen ein keratorefraktiver Eingriff aufgrund der hohen Ametropie nicht möglich ist.…”
Section: Diskussionunclassified
“…Langfristige Nachuntersuchungen sind erforderlich [22], da z. B. auch Fälle von rezidivierenden Verschlüssen von Laseriridotomien [19] im Rahmen der Entwick- …”
Section: Diskussionunclassified